Economic Aspects of the Spatial Management of Cities and Regions – An Outline of the Issues - Kudłacz, Tadeusz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
This paper provides a review of the main problems connected with the economic aspects of spatial management. After looking at the key terminology, it takes up the factors of spatial value. The essential part of the article is its discussion of a methodical approach to valuing space. It presents a set of the patterns that illustrate the elements of the valuation procedure.